Equity in initial health evaluation utilization among world trade center health program members enrolled during 2012–2022 - Ruiling Liu; Michael O’Reilly; Sarah Rockhill; Lillian Fu; Kendra C. Smith; Emma Butturini; Albeliz Santiago-Colón; Rachael L. Shaw; Kevin Pressley; Geoffrey M. Calvert (BMC Health Services Research)
Abstract Background The World Trade Center (WTC) Health Program, a limited federal healthcare program, provides medical monitoring and treatment for WTC-related conditions to eligible Responders and Survivors of the 9/11 terrorist attacks. Free initial health evaluations (IHE) represent the first step towards the Program’s goal of providing equitable and timely member access to healthcare. This study aimed to evaluate equity in IHE utilization among Program members to inform the development of targeted interventions. Methods This surveillance study used administrative and surveillance data collected from January 2012 through February 2024. It included Program members newly enrolled during 2012–2022 who completed an IHE or were alive for ≥ 1 year after enrollment. We conducted descriptive and multivariable logistic regression analyses. Outcomes of interest included timely IHE utilization (proportion of members completing an IHE within 6 months of enrollment) and any IHE utilization (proportion completing an IHE by February 2024). Factors of interest included member type, sex, age, race/ethnicity, preferred language, and urban/rural residence. Results 27,379 Responders and 30,679 Survivors were included. Responders were 89% male, 70% 45–64 years old at enrollment and 76% non-Hispanic White. Survivors were 54% male, 54% 45–64 years old at enrollment and 57% non-Hispanic White. Timely IHE utilization remained stable (~ 65%) among Responders, while for Survivors, it increased from 16% among those enrolled in 2017 to 68% in 2021. Timely IHE utilization was lower for younger members (enrolled < 45 years old vs. ≥ 65 years old, adjusted odds ratio [aOR] = 0.71, p < 0.001), rural residents, female Survivors (44% vs. 47% males, aOR = 0.87, p < 0.001), and Survivors who preferred non-English languages (39% vs. 46% who preferred English, aOR = 0.70, p < 0.001). Compared to non-Hispanic White members, non-Hispanic Black members had higher timely/any IHE utilization, while non-Hispanic Asian/Pacific Islander/Native Hawaiian and Hispanic Survivors had lower timely IHE utilization. Conclusions This study highlights Program achievements (e.g. increased timely IHE utilization among Survivors over time and higher timely/any IHE utilization among non-Hispanic Black members compared to non-Hispanic White members) and gaps in providing equitable IHE services to its members. The Program can develop tailored strategies to further improve equity in IHE utilization (e.g. working with providers to adopt/expand flexible IHE scheduling and increase non-English language capacity).